From the City to the Urban Assembly: Amman Metropolis at a High Price - Abu-Hussein, Mohammed; Al-Hamad, Zaid; Kakani, Anan; Tabbalat , Shereen; Abu Hamdiyah, Ayman (Dirasat: Human and Social Sciences, 2024)
Objectives: This study explores the reasons behind the rapid urban inflation of Amman, the capital city of Jordan, and its transformation from a traditional city to an expensive urban conglomerate. Particularly, it aims at identifying the causes of Amman's growth and expansion, exploring the negative effects of this growth on agricultural lands and traditional settlement patterns, and proposing alternative solutions such as decentralization. Methods: The descriptive approach was employed to analyze various sources such as studies, references, statistics, and maps documenting the growth sequence of Amman from its inception to the present day. Planning policies, which focused on the city's infrastructure and structure but neglected social and economic studies, contributed to its transformation into an expensive urban conglomerate. Results: It is proposed that Amman could be transformed into a genuine city by developing small, well-equipped new centers in the suburbs and implementing awareness programs to change the current administrative perception, which views the city merely as a congregation. This could enable the city to develop a strong, socially and culturally designed center. Further, decentralization is suggested as an effective alternative to address the negative impacts of Amman's prevailing urban agglomeration rooted in its traditional settlement pattern. Conclusion: A comprehensive approach is required that takes into account social and economic studies, along with the city's infrastructure and structure, to mitigate the adverse effects of urban expansion and growth. The study offers potential solutions that could help Amman confront the challenges associated with being a costly urban conglomerate and transition it into a proper city.